Recent Advances in Hole-Transporting Layers for Organic Solar Cells - Cinthya Anrango-Camacho; Karla Pavón-Ipiales; Bernardo A. Frontana-Uribe; Alex Palma-Cando (Nanomaterials, 2022)
Global energy demand is increasing; thus, emerging renewable energy sources, such as organic solar cells (OSCs), are fundamental to mitigate the negative effects of fuel consumption. Within OSC’s advancements, the development of efficient and stable interface materials is essential to achieve high performance, long-term stability, low costs, and broader applicability. Inorganic and nanocarbon-based materials show a suitable work function, tunable optical/electronic properties, stability to the presence of moisture, and facile solution processing, while organic conducting polymers and small molecules have some advantages such as fast and low-cost production, solution process, low energy payback time, light weight, and less adverse environmental impact, making them attractive as hole transporting layers (HTLs) for OSCs. This review looked at the recent progress in metal oxides, metal sulfides, nanocarbon materials, conducting polymers, and small organic molecules as HTLs in OSCs over the past five years. The endeavors in research and technology have optimized the preparation and deposition methods of HTLs. Strategies of doping, composite/hybrid formation, and modifications have also tuned the optical/electrical properties of these materials as HTLs to obtain efficient and stable OSCs. We highlighted the impact of structure, composition, and processing conditions of inorganic and organic materials as HTLs in conventional and inverted OSCs.